Why do women assume a supine position when giving birth? The perceptions and experiences of postnatal mothers and nurse-midwives in Tanzania - Lilian Teddy Mselle; Lucia Eustace (BMC, 2020)
Abstract Background Before the advent of Western medicine in Tanzania, women gave birth in an upright position either by sitting, squatting or kneeling. Birthing women would hold ropes or trees as a way of gaining strength and stability in order to push the baby with sufficient force. Despite the evidence supporting the upright position as beneficial to the woman and her unborn child, healthcare facilities consistently promote the use of the supine position. The purpose of this study was to explore the perceptions and experiences of mothers and nurse-midwives regarding the use of the supine position during labour and delivery. Methods We used a descriptive qualitative design. We conducted seven semi-structured interviews with nurse-midwives and two focus group discussions with postnatal mothers who were purposively recruited for the study. Qualitative content analysis guided the analysis. Results Four themes emerged from mothers' and midwives' description of their experiences and perceptions of using supine position during childbirth. These were: women adopted the supine position as instructed by midwives; women experience of using alternative birthing positions; midwives commonly decide birthing positions for labouring women and supine position is the best-known birthing position. Conclusion Women use the supine position during childbirth because they are instructed to do so by the nurse-midwives. Nurse-midwives believe that the supine position is the universally known and practised birthing position, and prefer it because it provides flexibility for them to continuously monitor the progress of labour and assist delivery most efficiently. Mothers in this study had no other choice than to labour and deliver their babies in the supine position as instructed because they trusted midwives as skilled professionals who knew what was best given the condition of the mother and her baby.